The role of inflammation in cervical cancer - Deivendran, S; Marzook, K Hezlin; Radhakrishna Pillai, M (Advances in experimental medicine and biology, 2014)
Knowledge regarding cervical cancer and human papillomavirus is expanding rapidly. Inflammation subsequent to viral infection is a driving force that accelerates cancer development. The infiltrated immune cells and their secretory cytokines along with chemokines and growth factors greatly contribute the malignant traits of cervical cancer. A better understanding of the mechanisms related to inflammation and cancer progression in terms of pathogen survival, cancer development, progression, and metastasis will lead to innovative approach for treating cancer.